Effects of Multimodal Operations on Urban Roadways. Issue 1 (January 2015) - Arnet, Kathrin; Guler, S. Ilgin; Menendez, Monica
Public transportation (e.g., buses) can provide more efficient urban transportation systems by carrying more people in the same space. A commonly used solution to prioritize this mode is to dedicate a lane for bus use only. However, the changes in system capacity are not clear for the use of a dedicated bus lane instead of completely mixed-use lanes. Even if the capacity of the dedicated bus lane were not fully used, this strategy could still increase car capacity in the remaining lanes in two ways: ( a ) buses traveling on a separate lane would eliminate conflicting bus maneuvers and ( b ) the reduced number of lanes available for cars could reduce the number of lane changes and could smooth traffic. This paper empirically analyzes differences in car capacity between ( a ) a mixed-use scenario without the influence of buses and a dedicated-lane scenario and ( b ) a mixed-use scenario with and without buses. Results show that with mixed-use lanes the car capacity per lane remains the same as compared with a dedicated-lane scenario. However, in mixed-use conditions, the presence of a bus in traffic flow can reduce capacity by 20%. Based on these findings, a simple analysis is carried out to compare passenger delay at urban signalized intersections with a mixed use versus dedicated bus lane. It is shown that passenger delay can be reduced with use of dedicated bus lanes if bus occupancies are relatively high or if car demand is low.